2016
DOI: 10.1177/1471301216647814
|View full text |Cite
|
Sign up to set email alerts
|

New relationships and intimacy in long-term care: The views of relatives of residents with dementia and care home staff

Abstract: Background There is limited research on what family members and frontline care home staff consider to be the best responses to the sexual expression of a person with dementia, whilst at the same time respecting relatives' feelings, managing their possible distress and conflict. Methods This exploratory study investigated the views of relatives and care workers of new relationships or sexual intimacy between care home residents with dementia, whilst still married to another person. It reports the themes that em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…We support the observation of many participants that residents have a right to privacy, and as long as residents are competent to make financial decisions elsewhere in their lives, they have a right to spend their own money on sex workers without the need for the facility to notify the family, or to seek their permission. We also found that both staff and family members often have a hazy understanding of how legal authorities such as powers of attorney relate to residents' sexual expression, and therefore, this is a particular area that warrants clear policy and education (Bauer et al, 2014;Wiskerke & Manthorpe, 2016). To include third parties unnecessarily on decisions about sex workers is at best institutional risk management, and at worst simply gossip.…”
Section: Policy Recommendationsmentioning
confidence: 89%
“…We support the observation of many participants that residents have a right to privacy, and as long as residents are competent to make financial decisions elsewhere in their lives, they have a right to spend their own money on sex workers without the need for the facility to notify the family, or to seek their permission. We also found that both staff and family members often have a hazy understanding of how legal authorities such as powers of attorney relate to residents' sexual expression, and therefore, this is a particular area that warrants clear policy and education (Bauer et al, 2014;Wiskerke & Manthorpe, 2016). To include third parties unnecessarily on decisions about sex workers is at best institutional risk management, and at worst simply gossip.…”
Section: Policy Recommendationsmentioning
confidence: 89%
“…An example of an especially restrictive approach is when the agent's decision to prohibit sexual expression is at odds with the resident's expressed desires. For instance, it is common for persons living with dementia in continuing care to develop new relationships with fellow residents, sometimes while they are married or in committed partnerships (Doll, 2013;Wiskerke & Manthorpe, 2018). This can be upsetting for community-dwelling spouses or partners who may then request that the new relationship be discontinued or that one of the residents be movedboth of which can be difficult for residents.…”
Section: Relational Dynamics Involving Care Staff and Agentsmentioning
confidence: 99%
“…More recently, a growing evidence base of psychosocial approaches to managing ISBs in people with dementia has developed. The perspective that is now accepted is that ISBs could be responses to contextual cues or unmet needs for intimacy that are innate, whether or not a person has dementia (Jones & Moyle, 2016;Kamel & Hajjar, 2003;Wiskerke & Manthorpe, 2018). Although there are few published and institutionally supported documents that include evidence-based behavioural recommendations for managing ISBs, some potentially useful strategies have been proposed as either stand-alone or supplemental interventions (International Longevity Centre -UK, 2011;Kettl, 2008;Syme, Lichtenberg, & Moye, 2016;Verdelho & Gonçalves-Pereira, 2017).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…In the context of LTC facilities, the presence of ISBs poses practical and ethical dilemmas since they have the potential to impinge on the rights of others (staff and residents) and thus need to be adequately monitored and managed. Staff have reported feelings of distress, negative attitudes and difficulties with managing ISBs, all of which may increase the burden of care (Higgins et al, 2004;Onishi et al, 2006;Wiskerke & Manthorpe, 2018) due to the perceived violation of moral rules, invasions of bodily privacy and concern about the impact of ISBs on others (Dupuis, Wiersma, & Loiselle, 2012).…”
Section: Introductionmentioning
confidence: 99%